An Improved Flowchart for Gabor Order Tracking with Gaussian Window as the Analysis Window. (28th December 2010) - Jin Jin, Yang Yang; Hao Hao, Zhiyong Zhiyong
Abstract : Based on simulations on the ability of the Gaussian-function windowed Gabor coefficient spectrum to separate order components, an improved flowchart for Gabor order tracking (GOT) is put forward. With a conventional GOT flowchart with Gaussian window, successful order waveform reconstruction depends significantly on analysis parameters such as time sampling step, frequency sampling step, and window length in point number. A trial-and-error method is needed to find such parameters. However, an automatic search with an improved flowchart is possible if the speed-time curve and order difference between adjacent order components are known. The appropriate analysis parameters for a successful waveform reconstruction of all order components within a given order range and a speed range can be determined.